Emancipatory Methodologies : Knowledge Production and (Re)existence of the Misak People in Colombia - Banguero Velasco, Rigoberto; Gruber, Valerie (PACHA, 2022)
Indigenous communities such as the Misak people in Colombia continue to struggle against the consequences of colonization and violence, but at the same time, they propose emancipatory methodologies of knowledge production. These practices towards epistemic justice are crucial to assure the (re)existence of indigenous peoples and their wisdom in Abya Yala. In this vein, our article sheds light on research methodologies rooted in Misak cosmogonies and processes to validate ancestral knowledge production. Through ethnographic and participatory action research in the indigenous reserve of Shura Manéla in the Colombian Cauca Department, we got insight into the spiral of persistent existence (espiral de pervivencia) and the law of origin of the Misak people. On this basis, we describe the Latá-Latá methodology reinvented by the community to recover their ancestral knowledge, and the Pachakiwa social cartography applied to depict their territorial relations. Moreover, we explain how collective validation processes work in practice. This serves to open up a transdisciplinary discussion on the potentials and the limitations of such vernacular research methodologies. We observe that healing from the trauma of colonization and inferiorization is a key driver of indigenous research processes. Therefore, developing further emancipatory methodologies based on equal subject-subject relations is an urgent task in the field of decoloniality. Learning from communities like the Misak is an invitation to become aware of the pluriversal complexity, listen to silenced sagacity, and find methods to pursue epistemic equality.
Keywords: Indigenous Research Methods; Emancipation; Misak; Colombia